Efficiency of Growth in an Organized Herd of Gir cattle in North Saurashtra Agro-climatic Region of Gujarat (Indian Journal of Animal Production and Management, 2024)
The present study was undertaken to find the efficiency of growth performance in Gir calves born  (N=52) and raised at Bull Mother Farm, Kamdhenu University, Amreli. The overall birth weight in Gir  calves was 24.66 ± 0.40 kg, male calves being significantly (P, 0.004) heavier (9.88%) at birth than  female calves. Irrespective of sex, the Gir calves weighed 66.83 kg at 3 months and 109.25 kg at 6  months of age, whereas yearling body weight was 192.82 kg. At 2 years of age, the Gir heifers  attained 263.57 ± 17.29 kg body weight, which was above the optimum/ desired breedable body  (240-250 kg). The body weight gains from birth to 3 month and from 3 to 6 month growth phases  were almost similar, values being 466.9 ± 12.81 and 468.94 ± 20.15 gm/day, respectively. After  attaining 1 year of age, the rate of body weight gain showed a diminishing trend, from 312.37 to  270.61 gm/day, with advancement of age. Relative body weight gain, irrespective of sex, was a  maximum of 172.88 ± 6.51 % in the birth to 3 month age group, followed by 63.66 ± 2.66% in the 3  to 6 month age group. The findings indicated that due care of the Gir calves, especially during birth  to 3 month age is vital to explore their growth potential, as relative weight gain of calves during this  phase is maximum (172.88%) for attaining early breedable body weight and in turn, reducing age at  first calving.
Keywords: Gir cattle; absolute growth rate; body weight gain; relative growth